Effect of led light on in vitro growth and developmentof Anoectochilus roxburghii - Gấm, Đỗ Thị; Chu Hoàng Hà, Chu Hoàng Hà Chu Hoàng Hà; Phạm Bích Ngọc, Phạm Bích Ngọc Phạm Bích Ngọc; Hưng, Nguyễn Khắc; Khôi, Phan Hồng; Bình, Hà Thị Thanh; Chương, Nguyễn Như; Nam, Lường Tú; Bình, Nguyễn Thị Thúy (Vietnam Journal of Biotechnology, 2018)
Recently, LED lighting technology has been developed fast and strongly. It has been widely used in many new fields. LEDs have been tested as an artificial light source during micropagation and tissue culture of various plants species as an alternative to traditional light sources to save energy and improve the efficiency of the culture process. In this study, effects of LED light at different wavelengths and luminous intensities on growth of Anoectochilus roxburghii’s buds in vitro were investigated. Anoectochilus’s buds were cultured under the different light conditions, such as LED in monochromatic red (R), LED in monochromatic green (B) , LED in the green and red light combining with warm white light (W) in different ratios (BRW 1, BRW2, BRW3 and BR). After 3 months of culture, the results showed LED B at strong luminous intensity (79 ± 3 μmol.m-2.s-1) inhibited the growth and development of Anoectochilus roxburghii. In contrast, BR LED with low luminous intensity (30 ± 1μmol.m-2.s-1) had made a positive effect on growth and development of Anoectochilus roxburghii. The plant height (5,88 cm), root length (1,33 cm), fresh plant weight (0,169 g/plant), leaf area (0,82 cm2), fresh leaf weight (18,33 mg/leaves) of plants in vitro were found higher than those of plants grown under T5 fluorescent lighting conditions (as control). Besides, chlorophyll a, chlorophyll b and total chlorophyll content of leaves (285,40 µg/g, 196,40 µg/g, 481,80 µg/g respectively) were higher than in the control and other versions of LED combine. The results also showed that the LED light with combined ratio of BR = 1: 4 at luminous intensity of 30 μmol.m-2.s-1 were suitable for the growth of Anoectochilus roxburghii. Therefore, BR LED (1:4) light condition should be replaced fluorescent light sources in vitro culture of Anoectochilus roxburghii in future.